2000
DOI: 10.1086/309252
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Photodissociation Region:HST/NICMOS Imaging of NGC 7027

Abstract: We report results from a Hubble Space Telescope (HST) and Near-Infrared Camera and Multiobject Spectrometer (NICMOS) program to study the distribution of hot neutral (molecular hydrogen) and ionized circumstellar material in the young planetary nebulae NGC 7027. HST/NICMOS provided very high spatial resolution imaging in line and continuum emission, and the stability and large dynamic range needed for investigating detailed structures in the circumstellar material. We present dramatic new images of NGC 7027 th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
125
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(145 citation statements)
references
References 50 publications
20
125
0
Order By: Relevance
“…Aside from faint [O i] emission, the outer lobes are seen only in scattered light at visual wavelengths (Balick 1999). This structure, with [Fe ii] bulbs inside a thin H 2 skin, is similar to the double-shell structure in the nebula surrounding Car (Smith 2002 ( Welch et al 1999;Hora & Latter 1996) and NGC 7027 (Latter et al 2000). In HST images, the outer and inner shells of M2-9 distinguish themselves in low-and high-excitation emission lines like [O i] and [O iii], respectively (Balick 1999).…”
Section: Introductionsupporting
confidence: 57%
“…Aside from faint [O i] emission, the outer lobes are seen only in scattered light at visual wavelengths (Balick 1999). This structure, with [Fe ii] bulbs inside a thin H 2 skin, is similar to the double-shell structure in the nebula surrounding Car (Smith 2002 ( Welch et al 1999;Hora & Latter 1996) and NGC 7027 (Latter et al 2000). In HST images, the outer and inner shells of M2-9 distinguish themselves in low-and high-excitation emission lines like [O i] and [O iii], respectively (Balick 1999).…”
Section: Introductionsupporting
confidence: 57%
“…Morphologically, NGC 7027 consist of a bright rim-like structure with an attached faint shell, surrounded by a molecular shell seen in emission from H 2 (Latter et al 2000, Fig. 7 therein).…”
Section: Ngc 7027mentioning
confidence: 99%
“…1a). The core region clearly suffers a large degree of spatially irregular (clumpy) extinction in the optical, whereas, in the near-infrared (Kastner et al 1994;Latter et al 2000, hereafter L2000) and radio (Masson 1989), the ionized region is revealed to be an elliptical shell. Surrounding this shell, but largely interior to the system of concentric rings, is a photodissociation region with a remarkable cloverleaf or double-ring morphology that is best seen in near-infrared H 2 and polycyclic aromatic hydrocarbon emission (Graham et al 1993;Kastner et al 1996;L2000).…”
mentioning
confidence: 99%